STABILITY ANALYSIS OF DEFECT AROUND PARTICLES IN EUTECTIC COMPOSITE CERAMIC - YU JinFeng; LIU XieQuan; NI XinHua; FU YunWei (Jixie qiangdu)
The defect arising from the thermal coefficient mismatch of different phases was an important factor of reducing strength in eutectic composite ceramic. Based on the equivalent inclusion method and the interaction direct derivative（ IDD）estimate,stress intensity factor of annular defect under residual stress field and applied loading was calculated,and annular defect stability was analyzed. And the influence of particle stiffness,shape and volume fraction was investigated. Results indicated that,the crack nucleation was most easily produced in the oblate particle; stiff particles caused average applied stress reduced in matrix,and it reduced greater when the stiff particle was prolate elliptic,while the soft particle had the contrary effect. Stress intensity factor of defect was controlled by residual stress as the defect extension was small while it was controlled by applied stress for large defect extension. Prolate elliptic particle was beneficial to improve strength.